2020
DOI: 10.1371/journal.pone.0230618
|View full text |Cite
|
Sign up to set email alerts
|

Reference values of physiological 18F-FET uptake: Implications for brain tumor discrimination

Abstract: The aim of this study was to derive reference values of 18F-fluoro-ethyl-L-tyrosine positron emission tomography (18F-FET-PET) uptake in normal brain and head structures to allow for differentiation from tumor tissue. Materials and methods We examined the datasets of 70 patients (median age 53 years, range 15-79), whose dynamic 18F-FET-PET was acquired between January 2016 and October 2017. Maximum standardized uptake value (SUVmax), target-to-background standardized uptake value ratio (TBR), and time activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 51 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…Previous studies show that the intra- and inter-reader variability associated with current, most common methods of selecting regions of background activity (2D circular region of interest or 3D spherical VOI) result in background SUV changes of up to ± 8% [ 6 ]. This large variability has been mostly attributed to the variable size and insufficient inclusion of different types of tissue within the selected 2D reference region, and to the imprecise and arbitrary selection of the positioning of the 3D reference region, which could result in the inclusion of areas with notably higher 18 F-FET uptake, such as venous structures and areas of grey matter [ 25 ]. The use of a crescent-shape VOI has been accepted and recommended by the joint EANM/EANO/RANO practice guidelines/SNMMI procedure standards as a solution to these issues, as this method allows for the inclusion in the reference region of a larger volume of tissue from both white and grey matter, and for the morphological adaptation of the reference region such that to exclude ventricles and venous sinuses [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies show that the intra- and inter-reader variability associated with current, most common methods of selecting regions of background activity (2D circular region of interest or 3D spherical VOI) result in background SUV changes of up to ± 8% [ 6 ]. This large variability has been mostly attributed to the variable size and insufficient inclusion of different types of tissue within the selected 2D reference region, and to the imprecise and arbitrary selection of the positioning of the 3D reference region, which could result in the inclusion of areas with notably higher 18 F-FET uptake, such as venous structures and areas of grey matter [ 25 ]. The use of a crescent-shape VOI has been accepted and recommended by the joint EANM/EANO/RANO practice guidelines/SNMMI procedure standards as a solution to these issues, as this method allows for the inclusion in the reference region of a larger volume of tissue from both white and grey matter, and for the morphological adaptation of the reference region such that to exclude ventricles and venous sinuses [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significant reduction in values of CoV, which had median values of 0% for both CTRL SUV mean and BTV, is mainly due to the elimination of biases involved in the individual selection of placement of the background reference region, but also to the consideration of the size and percentage of involvement of different tissue types and brain structures which are reflected in the tumour lesion. Taking into account the size and the relative involvement of different tissue types in the background reference region is particularly important as recent studies have demonstrated that selected normal brain structures have intrinsically high physiological 18 F-FET uptake, and that patient-specific factors, such as gender and body mass index, can affect values of 18 F-FET uptake in the brain in a patient-specific manner [ 7 , 25 ]. Consequently, if the tumour is small and located in an area of the brain with intrinsically high 18 F-FET uptake, selecting a large background reference VOI from other areas of healthy brain might result in an underestimation of the background reference SUV and, in turn, in an overestimation of TBR values.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25] Few studies include patients with a variety of glioma grades (II-IV), predominantly astrocytic and oligodendroglial histology, with very few studies of GBM. 26,27 Second, all our patients have received a standard radiotherapy (RT)-TMZ protocol (Stupps regimen), unlike some of the earlier studies where nonstandard-of-care treatments were offered. Variable time-points post-treatment also affect the performance of radiotracers, which is seen in some studies.…”
Section: Discussionmentioning
confidence: 99%
“…The published literature on diagnostic accuracy of 18 F‐FET PET for distinguishing tumor recurrence from post‐treatment changes is not scarce, but suffers from lack of standardization of protocols, improper patient selection, and fixed imaging time‐points 22–25 . Few studies include patients with a variety of glioma grades (II–IV), predominantly astrocytic and oligodendroglial histology, with very few studies of GBM 26,27 . Second, all our patients have received a standard radiotherapy (RT)‐TMZ protocol (Stupps regimen), unlike some of the earlier studies where nonstandard‐of‐care treatments were offered.…”
Section: Discussionmentioning
confidence: 99%
“…This ( 18 F-DOPA) PET could be applied to assess the volume of remaining gliomas in the patient, Parkinson's syndrome, and focal hyperinsulinemia in infants, which was a perfect complement to the traditional detection technology. Except that, other types of fluorinated compounds were also used as PET tracers for cancer and tumor detection, such as 18 F-PSMA-1007 (Dietlein et al 2020 ), l -2- 18 F-FAMP, d -2/3/4- 18 F-FAMP and l -3- 18 F-FAMT (Hanaoka et al 2019 ; Mahendra et al 2020 ; Shimizu et al 2019 ), ( 18 F-FBPA) (Romanov et al 2020 ), 18 F-fluoro-ethyl- l -tyrosine ( 18 F-FET) (Fuenfgeld et al 2020 ; Marner et al 2019 ), 6- 18 F-fluoro-meta-tyrosine ( 18 F-FMT) (Badin et al 2019 ; Kojima et al 2019 ; Miyamoto et al 2020 ), N -[ 18 F]-fluoropropylJDTic (Schmitt et al 2017 ), 2-(3-(1-carboxy-5-[(6- 18 F-fluoro-pyridine-3-carbonyl)-amino]-pentyl)-ureido)-pentanedioic acid ( 18 F-DCFPyL) (Jansen et al 2019 ; Rousseau et al 2019 ; Rowe et al 2020a , 2020b ), 5- 18 F-fluoro- l -amino suberate ( 18 F-FASu) (Alluri et al 2020 ; Colovic et al 2019 ), 4-borono-2- 18 F-fluoro- l -phenylalanine fluorine substituted 3-azabicyclo hexane (Chen et al 2019b ), and [ 18 F]FDA-PEG-biotin/tetrazine (Lowe et al 2018 ). Therefore, PET tracers based on new fluorinated compounds will play an increasing role in the field of visual detection technology.…”
Section: Applications Of Fluorinated Compoundsmentioning
confidence: 99%